Penyuluhan Implementasi Program Sekolah Penggerak Berdasarkan SK Kemendikbud Nomor 162 Tahun 2021 di SD Negeri 13 Rantau Alai - Firmansyah Firmansyah; Erisa Ardika Prasada (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
This community service activity aims to assist partners in increasing the understanding of educators and education personnel of the Merdeka Belajar Curriculum and the Mover School Program. The method of implementing the service is in the form of educational activities in the form of counseling which was carried out on February 5-17, 2023 with an activity workflow of four stages, namely: planning stage, implementation stage, evaluation stage, and reporting stage. This activity has been completed by meeting the predetermined achievement targets. These achievements can be seen from the enthusiasm of the participants in participating in counseling activities and being active in question and answer activities and discussions. In reviewing the evaluation of activities, the implementation team considered that the implementation of this service activity could not be separated from the maximum support from partners through the preparation of facilities during the event and the enthusiasm of participants in participating in counseling activities. The inhibiting factors of the activity include: time constraints, participant attendance that is not optimal, and the remote location of partners, far from the city and in an internet blind spot.